Pengembangan Kemampuan Dasar Siswa Melalui Praktik Pembelajaran Tematik - Suherman; Suni Samsuni; Media Sucahya; Indrianti Azhar Firdausi; Sulasno (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This service activity aims to increase students' insight and motivation towards the importance of Information Technology (ICT), English, and the Environment at UPT SDN Wanakarta 1. Teaching and Learning Activities (KBM) were carried out for 5 meetings involving students from grade 1 to grade 6. The learning method used is learning while playing so that the material presented can be easily accepted by students. The results showed that the KBM conducted succeeded in increasing students' insight and motivation. This is shown by the results of the Pre-Test and Post-Test which show an increase in student understanding of ICT material by 88%, English by 90%, and Environment (animal names) by 100%. The success of this KBM is due to several factors, namely: (1) Selection of materials that are in accordance with the needs and interests of students, (2) Use of interesting and interactive learning methods and (3) Motivation and dedication of the presenters. Based on the results of this study, it can be concluded that KBM is an effective way to increase students' insight and motivation. Therefore, KBM needs to be continuously developed and implemented in other schools.